STUDY ON INTEGRATION OF IMPLANTS INSERTED INTO MAXILLARY GROWTHS AUGMENTED BY SINUS LIFTING INTERVENTIONS - Mihai Nedelcu; Mihaela Petre; Valentin Sirbu (Amaltea Medical Publishing House, 2018)
Oral implantology offers the possibility of restoring, through fixed prosthetics, the maxillary arches with loss of lateral teeth. In order to insert implants in these regions, it is often necessary to use interventions that can increase the bone supply, since both the quality and the bone quantity are lower in the respective anatomical areas. It is therefore necessary to use sinus lift, either through the crestal approach or by lateral approach, by making a window in the lateral wall of the maxillary sinus. Each of these approaches has advantages and disadvantages and addresses specific clinical cases, and all of that the clinician needs to know correctly, in order to achieve the expected final results.